2018
DOI: 10.1360/n972018-00801
|View full text |Cite
|
Sign up to set email alerts
|

Identification and gene mapping of a panicle apical abortion mutant (<italic>paa1331</italic>) in rice

Abstract: 部一次枝梗退化 [1]. 目前克隆的控制穗顶部退化的基 因有PAA2(panicle apical abortion2)、TUT1(tutou1)、 OsALMT7(aluminum-activated malate transporter)、 SPL6(squamosal promoter-binding protein-like) [2~6] .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Due to the further unavailability of InDel markers in this region, we performed a MutMap assay to find any mutation in the primary mapped region by following a method of Abe et al [58] . MutMap whole genome sequencing (Illumina HiSeq 2500 platform) revealed an SNP index of 1 due to the presence of a single nucleotide mutation in ( Os04g0483400 ) LOC_Os04g40720 [52] . Consistent with the primary mapping by SSR markers, Mutmap results showed an SNP (A > G) located between the previously mapped region of SSR markers RM252 and RM5979.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the further unavailability of InDel markers in this region, we performed a MutMap assay to find any mutation in the primary mapped region by following a method of Abe et al [58] . MutMap whole genome sequencing (Illumina HiSeq 2500 platform) revealed an SNP index of 1 due to the presence of a single nucleotide mutation in ( Os04g0483400 ) LOC_Os04g40720 [52] . Consistent with the primary mapping by SSR markers, Mutmap results showed an SNP (A > G) located between the previously mapped region of SSR markers RM252 and RM5979.…”
Section: Resultsmentioning
confidence: 99%
“…Current study presents the further genetic analysis and functional validation of our previous preliminary study of a gene mapped on chromosome 4 controlling panicle abortion phenotype (Hou et al ., 2018). However, the its further follow up genetic analysis and functional analysis was not carried out.…”
Section: Introductionmentioning
confidence: 78%
“…In F 1 generations of both populations, all plants did not show degeneration phenotype. Genetic analysis of these population revealed that a single recessive gene controls the phenotype of panicle degeneration in apa1331(Hou et al, 2018) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations